2021
DOI: 10.3390/ijms22073582
|View full text |Cite
|
Sign up to set email alerts
|

The Role of BDNF in Experimental and Clinical Traumatic Brain Injury

Abstract: Traumatic brain injury is one of the leading causes of mortality and morbidity in the world with no current pharmacological treatment. The role of BDNF in neural repair and regeneration is well established and has also been the focus of TBI research. Here, we review experimental animal models assessing BDNF expression following injury as well as clinical studies in humans including the role of BDNF polymorphism in TBI. There is a large heterogeneity in experimental setups and hence the results with different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 151 publications
2
24
0
1
Order By: Relevance
“…Inflammatory biomarkers were chosen to investigate chronic inflammation related to psychological and brain trauma. Brain derived neurotropic factor (BDNF) was chosen based on its association with brain injury both in regulating neurodegeneration and neural protection [10][11][12] and in recovery [13,14]. We hypothesized that close blast exposure and mTBI would be related to increases in pro-inflammatory markers, as measured by IL-6, TNFα, and eotaxin-1, and decreases in antiinflammatory markers, such as interleukin-10 (IL-10).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory biomarkers were chosen to investigate chronic inflammation related to psychological and brain trauma. Brain derived neurotropic factor (BDNF) was chosen based on its association with brain injury both in regulating neurodegeneration and neural protection [10][11][12] and in recovery [13,14]. We hypothesized that close blast exposure and mTBI would be related to increases in pro-inflammatory markers, as measured by IL-6, TNFα, and eotaxin-1, and decreases in antiinflammatory markers, such as interleukin-10 (IL-10).…”
Section: Introductionmentioning
confidence: 99%
“…BDNF is expressed by neurons, astrocytes and various immune cells. BDNF protects neurons and supports OPC proliferation in traumatically injured nerve tissues ( 45 ). We observed that BDNF from neurons attenuated EAE symptoms, in agreement with a previous study ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The coordination of the BDNF and TrkB receptors governs a wide range of neural activities, including neuronal survival, differentiation, migration, axonal sprouting, synaptogenesis, plasticity, and the enhancement of long-term potentiation (LTP), which influences learning and memory [86][87][88]. Growing studies focusing on BDNF have emerged, but there are discrepancies among the results of BDNF expression at different post-injury times, regions in the CNS, genetic polymorphisms, and clinical outcomes [89][90][91].…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
“…The BDNF protein possesses a single-nucleotide polymorphism (SNP) site at rs6265, at the 66-amino acid position, which results in the replacement of wildtype Val with Met (Val66Met, valine to methionine) [92]. Although other SNPs of BDNF such as rs71244, rs1519480, and rs1153659 have been reported to influence the outcome after TBI, the most studied polymorphism of BDNF in humans is rs6265 (Val66Met) [89]. The frequency of the Met66 allele is approximately 25-32% in Caucasian populations and 40-50% in Asian populations [93].…”
Section: Single-nucleotide Polymorphism Of Bdnfmentioning
confidence: 99%